Analysis of Chromium (Cr) Heavy Metal Content in Sediments and Mangrove Roots Avicennia marina in the Wonorejo Mangrove Ecosystem Area Surabaya - garin pratama, choirul; Prayogo, Prayogo; Isroni, Wahyu (Journal of Marine and Coastal Science, 2025)
The mangrove area in Wonorejo is quite large and water sources from various areas have the potential to be sources of chromium. One of the mangrove species in this area is Avicennia marina. Avicennia marina plays an important role in reducing pollution. Based on this, a study was conducted to analyze the chromium content in sediment and roots of mangrove A. marina in the Wonorejo area. This study was descriptive with the stages of exploration, observation, and analysis, namely exploring and observing A. marina, taking samples in the field and analyzing samples in the laboratory. The subjects of this study were the roots and sediments of A. marina taken from two stations with three different points by determining the location using purposive random sampling. The chromium levels in the roots and sediments were tested using the Atomic Absorption Spectrophotometer (AAS) method. The data on Cr levels in roots and sediments were analyzed using quantitative descriptive statistics and analyzing the quality of sediments and roots of A. marina in the mangrove ecosystem with safe limit values. The results of this study are: 1) The Cr content in the sediment in the Jagir River was the highest at 1 mg/kg, while in the Afur River the highest was 0.82 mg/kg, 2) The Cr content in the roots of A. marina in the Jagir River is the highest at 2.8 mg/kg, while in the Afur River the highest is 2.5 mg/kg, and 3) The Cr content in the sediment has exceeded the safe threshold of 2.5 mg/kg and the Cr content in the roots has also exceeded the safe threshold of 0.05 mg/kg.